2019
DOI: 10.1063/1.5112177
|View full text |Cite
|
Sign up to set email alerts
|

A new and efficient numerical method for the fractional modeling and optimal control of diabetes and tuberculosis co-existence

Abstract: The main objective of this research is to investigate a new fractional mathematical model involving a nonsingular derivative operator to discuss the clinical implications of diabetes and tuberculosis coexistence. The new model involves two distinct populations, diabetics and nondiabetics, while each of them consists of seven tuberculosis states: susceptible, fast and slow latent, actively tuberculosis infection, recovered, fast latent after reinfection, and drug-resistant. The fractional operator is also consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
80
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 171 publications
(80 citation statements)
references
References 29 publications
0
80
0
Order By: Relevance
“…We know that many researchers are working on fractional differential equarions from different point of view (see, for example, ( [1][2][3][4][5][6][7][8][9][10][11][12] and [13]). In 2015, a new fractional derivative introduced entitled Caputo-Fabrizio and some researchers tried to obtain new techniques for studying of distinct integro-differential equations via the new derivation (see, for example, [14][15][16][17][18][19]) and new fractional models and optimal controls of different phenomena with the non-singular derivative operator (see, for example, [20][21][22][23][24] and [25]). Also, there has been published a lot of work about physical studies on fractional calculus and new aspects of fractional different models with Mittag-Leffler law (see, for example, [26][27][28][29] and [30]).…”
Section: Preliminariesmentioning
confidence: 99%
“…We know that many researchers are working on fractional differential equarions from different point of view (see, for example, ( [1][2][3][4][5][6][7][8][9][10][11][12] and [13]). In 2015, a new fractional derivative introduced entitled Caputo-Fabrizio and some researchers tried to obtain new techniques for studying of distinct integro-differential equations via the new derivation (see, for example, [14][15][16][17][18][19]) and new fractional models and optimal controls of different phenomena with the non-singular derivative operator (see, for example, [20][21][22][23][24] and [25]). Also, there has been published a lot of work about physical studies on fractional calculus and new aspects of fractional different models with Mittag-Leffler law (see, for example, [26][27][28][29] and [30]).…”
Section: Preliminariesmentioning
confidence: 99%
“…Such models have been extensively studied in the literature. On the other hand, it was shown that in many applications, the use of fractional derivatives provide more realistic models than those obtained via standard derivative (see, eg, previous studies and the references therein). Because of the above reason, the study of fractional models received a great attention form many reserchers.…”
Section: Introductionmentioning
confidence: 99%
“…We analyze the interactions between various tumor cell populations and immune system via a system of fractional differential equations (FDEs), 17 mathematical model for a dengue fever outbreak based on a system of fractional differential equations, 18 and fractional mathematical model involving a nonsingular derivative operator to discuss the clinical implications of diabetes and tuberculosis coexistence. 19 We consider a recently introduced fractional operator with Mittag-Leffler nonsingular kernel. We indicate that the complex behavior of many physical systems is realistically demonstrated via the fractional calculus modeling and also developed the fractional quantum mechanics and proved the hermiticity property of the Hamilton operator in fractional sense, 20,21 and some others techniques used in other works 22,23 are very helpful to demonstrate the results.…”
Section: Introductionmentioning
confidence: 99%